Đề xuất áp dụng mô hình quản lí chất lượng tổng thể (TQM) trong kiểm định chất lượng giáo dục ở trường trung học cơ sở - Nguyễn, Anh Việt; Trần, Văn Trung (Tạp chí Giáo dục, 2025)
Educational quality assessment is an important management task and a key measure to improve schools’ educational quality. The application of the total quality management (TQM) model in educational quality assurance provides secondary schools with a comprehensive framework to continuously improve teaching, management and student learning outcomes. This article presents some theoretical issues on quality assurance, analyzes the total quality management model, thereby proposing the process of applying TQM in educational quality assessment in secondary schools and some recommendations for implementation. By promoting cooperation, enhancing transparency and focusing on continuous quality improvement, TQM can help schools build a more comprehensive and effective quality management system, benefiting both students and the wider educational community. Through this approach, secondary schools can meet and exceed the defined educational standards, ultimately improving the quality of education.